Warmed, humidified CO(2) insufflation benefits intraoperative core temperature during laparoscopic surgery: A meta‐analysis - Dean, Meara (Asian J Endosc Surg, 2016)
BACKGROUND: Intraoperative hypothermia is linked to postoperative adverse events. The use of warmed, humidified CO(2) to establish pneumoperitoneum during laparoscopy has been associated with reduced incidence of intraoperative hypothermia. However, the small number and variable quality of published studies have caused uncertainty about the potential benefit of this therapy. This meta‐analysis was conducted to specifically evaluate the effects of warmed, humidified CO(2) during laparoscopy. METHODS: An electronic database search identified randomized controlled trials performed on adults who underwent laparoscopic abdominal surgery under general anesthesia with either warmed, humidified CO(2) or cold, dry CO(2). The main outcome measure of interest was change in intraoperative core body temperature. RESULTS: The database search identified 320 studies as potentially relevant, and of these, 13 met the inclusion criteria and were included in the analysis. During laparoscopic surgery, use of warmed, humidified CO(2) is associated with a significant increase in intraoperative core temperature (mean temperature change, 0.3°C), when compared with cold, dry CO(2) insufflation(.) CONCLUSION: Warmed, humidified CO(2) insufflation during laparoscopic abdominal surgery has been demonstrated to improve intraoperative maintenance of normothermia when compared with cold, dry CO(2.)